The Influence of E-Learning Model Web Enhanced Course to Conceptual Understanding and Self Regulated Learning in Mathematics for Elementary School Students - Arifin, Fatkhul; Herman, Tatang (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract This study is aimed to analyze students’ conceptual understanding and their self-regulated learning in mathematics between students who are treated using the e-learning model web enhanced course and those who are taught with the power point and to find out the appropriate e-learning design in learning math for elementary school. This study was conducted through quasi-experiment with a pre test-post test control group design. The population of this study is all of the 5thgrade students of private Islamic Elementary School (MI) in Jakarta, while the sample is taken from two classes of the population. The instruments used in this study are the essay, questionnaire, and observation sheet. The results showed that 1) students’ conceptual understanding of mathematics using e-learning model web enhanced course is better than students who get the learning using power point, 2) students’ self-regulated learning treated using e-learning model web enhanced course is better than students’ who get the learning using power point, 3) e-learning design that fits in the learning of mathematics in primary schools is e-learning design, incorporating text, images, and animations as well as providing convenience for group discussion. Based on these results it can be concluded that the e-learning web-enhanced model affects the conceptual understanding of mathematics and self-regulated learning of elementary school students.   Abstrak Studi ini bertujuan untuk menganalisa pemahaman konseptual siswa dan pembelajaran mandiri dalam matematika antara siswa yang diperlakukan menggunakan pembelajaran berbasis internet dan siswa yang diajarkan menggunakan power point dan untuk menemukan bentuk pembelajaran berbasis internet yang tepat dalam pembelajaran matematika untuk sekolah dasar. Studi ini diadakan melalui quasi-experiment dengan bentuk pre test dan post test. Populasi studi ini adalah seluruh siswa kelas 5 MI di Jakarta, sedangkan sampel diambil dari dua kelas dari keseluruhan populasi. Instrument yang digunakan dalam studi ini adalah essay, questionnaire, dan lembar observasi. Hasil dari studi ini menunjukkan bahwa 1) pemahaman konseptual siswa dalam matematika dengan menggunakan pembelajaran berbasis internet lebih baik dari pada siswa yang belajar menggunakan power point, 2) pembelajaran mandiri siswa yang menggunakan model pembelajaran berbasis internet lebih baik dari pada siswa yang belajar menggunakan power point, 3) bentuk pembelajaran berbasis internet yang cocok dalam belajar matematika untuk sekolah dasar adalah bentuk pembelajaran berbasis internet, memasukan teks, gambar, dan animasi senyaman mungkin untuk diskusi kelompok. Berdasarkan hasil di atas dapat disimpulkan bahwa model pembelajaran berbasis internet mempengaruhi pemahaman konseptual pelajaran matematika dan pembelajaran mandiri siswa sekolah dasar.   How to Cite : Arifin, F. Herman, T. (2017). The Influence of E-Learning Model Web Enhanced Course to Conceptual Understanding and Self Regulated Learning in Mathematics for Elementary School Students. TARBIYA: Journal of Education in Muslim Society, 4(1), 45-52. doi:10.15408/tjems.v4i1.5536. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.5536